Modeling and Simulation of Relocation of a Production in SIMPRO-Q Web Based Educational Environment - Lengyel, Lubomir; Zgodavova, Kristina; Bober, Peter (International Journal of Advanced Corporate Learning (iJAC), 2012)
The aim of this paper is to show the how to get new knowledge and skills through solving production relocation situations in a continuously changing global environment. The used methods model and simulate the related risks, using web based learning environment of Quality Management Role Play Simulation (SIMPRO-Q). The presented methods are applicable also in engineering education. During simulations, the role-players make both quantitative and qualitative decisions regarding management of critical situations during production relocation. Experiences from relocation production project in industry are discussed at the end of the paper.